2017
DOI: 10.1044/2016_jslhr-s-15-0355
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Vowel Centralization in Dysarthria: A Comparison of Methods

Abstract: The procedures researchers use to assess articulatory impairment can significantly alter the strength of relationship between acoustic and perceptual measures. Procedures that maximize this relationship are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…These procedures are consistent with general practice and recommendations for formant analysis using LPC and FFT [34, 35, 36, 37]. Because we have observed that the temporal midpoint of the vowel does not always correspond to a formant steady state, we used vowel-specific time points as defined by Derdemezis et al [31] and similar to criteria used others [38]:]:…”
Section: Methodsmentioning
confidence: 88%
“…These procedures are consistent with general practice and recommendations for formant analysis using LPC and FFT [34, 35, 36, 37]. Because we have observed that the temporal midpoint of the vowel does not always correspond to a formant steady state, we used vowel-specific time points as defined by Derdemezis et al [31] and similar to criteria used others [38]:]:…”
Section: Methodsmentioning
confidence: 88%
“…Speech disturbances may be the result of lack of muscular coordination (ataxia) and may appear with various intensities (from mild to severe) in traumatic brain injury, progressive supranuclear palsy, Parkinson's disease Wilson's disease, cerebral palsy, multiple sclerosis, Huntington's disease, hydrocephalus, stroke, brain tumor, Freidreich's ataxia, cerebellar ataxia, and spinocerebellar ataxia (10). 'Apraxia' (with reference to speech disorders), or 'apraxia of speech' (AOS) is a term introduced in the 1960s for naming a set of motor speech disorders due to a large number of causes, including but not limited to aphasia or dysarthria (11).…”
Section: Dysarthria and Dysarthric Speechmentioning
confidence: 99%
“…The so-called vowel space is simply the area of the polygon determined in the plane of the first two formants (F1 and F2) by the 'average' vowels pronounced by a subject. The analysis of formant centralization was found effective in explaining the voice quality ratings by listeners (perceptual rating) by Fletcher et al (10). Basically, the vowel centralization is computed as a function of the values of the first two formants for a specified subgroup of vowels.…”
Section: Dysarthria and Dysarthric Speechmentioning
confidence: 99%
“…A longstanding challenge for speech research has been to develop acoustic metrics predictive of intelligibility for normal speakers as well as for clinical populations, such as individuals with dysarthria. Efforts to date have largely focused on metrics of vowel segmental integrity derived from the first (F1) and second (F2) formant frequencies [1,2,3,4,5,6,7]. Vowel space area (VSA) refers to the two-dimensional quadrilateral space formed by F1 and F2 measured at a static point in time for the four English peripheral vowels (/i/, /ae/, /a/, and /u/) or non-peripheral vowels (/I/, /U/, /2/, and /E/) [5]; for the purposes of this study, we will focus on peripheral-VSA only.…”
Section: Introductionmentioning
confidence: 99%
“…Although the strength of the relationship varies substantially across studies, larger VSAs, which indicate increased articulatory-acoustic distinctiveness, are associated with increased intelligibility [6,7,8]. Procedures for optimizing the strength of association between perceived speech adequacy and vowel metrics requiring static measures of F1 and F2 have recently been proposed [7]. However, VSA and related metrics for quantifying acoustic distinctiveness among vowel categories have several limitations.…”
Section: Introductionmentioning
confidence: 99%